Caracterização do desenvolvimento rural sustentável em assentamentos de base agroecológica na Região Oeste do Paraná - Dri, Ricardo (2016)
The agriculture and livestock have provided food for the entire world population. That food production must be made from renewable resources, with proper use of water, soil maintenance, seeking a better redistribution of land, fixing the man to the field, using family labor, producing healthy foods, with reduced use chemicals and environmental protection. Thus this research aimed to analyze the rural sustainability in agroecological base settlements in the western region of Paraná, through the characterization of the three main pillars of rural sustainability: social, environmental and economic. The work was carried out from September 2014 to December 2015 among the peasants agrarian reform settlements that have agroecological principles of production. Sixty seven production systems in four slums of western Paraná were taken as reference. Data were collected through a semistructured questionnaire guide, in order to characterize the systems. Data were statistically analyzed with the help of IBM SPSS Statistics®18.0.e Microsoft Office Excel software through averages, cross tabulation and graphics. The agrarian reform settlements in the western region of Paraná are reaching social, the peasant families are surviving the earth and producing diverse, even the producers having low education, are seeking new information, participating collectively through cooperatives. Even not having adequate and sufficient machinery, and do not perform the management activities are achieving sustainability, because the systems are producing diversified, and the surplus production are being marketed. Through the environmental sustainability indicators it is concluded that improvements are needed in monitoring and soil management, garbage disposal, and waste of animals, and care of the waters of the dams, if contacted, the low use of pesticides and chemical fertilizers on properties. This study opens perspectives for further studies with a larger number of producers in an attempt to determine if there are other factors and what these factors are related to sustainability